Analysis of The Effect of Amount of Money Supply (JUB), Exchange Rate, Profit Sharing And Interest Rate on The Inflation 2011-2017: Islamic and Conventional M1 Comparative Study - Imam Haryadi; Wahid Ilhami (University of Darussalam Gontor, 2019)
Inflation is one of the effects of a prolonged economic crisis that hit any country. Inflation is a situation where there is an increase in general prices which continues over the long term. The objective of this research is to analyze the effect of the Amount of Money Supply and Exchange Rate, Interest Rate, Return Sharia against Inflation Rate in Indonesia. The type of this research is a quantitative study, research to explain the influence of independent variables to dependent variables. Dependent Variable used is Inflation Rate (percentages), Independent Variables are Money Supply, Exchange Rate (Indonesian Rupiah to US Dollar), Interest Rate, Return Sharia. The models will be calculated with VECM (Vector Error Correction Model) as it easy to calculate and interpret. In this case a correlation between dependent variables and independent variables. To determine the inflation rate effect from 2011-2017.The result of this research determines that in long term Independent variables has significant influence to Dependent variable (Inflation). Even in Islam and Conventional side. One of variable such as M1 in Islam has result 5.34041, its indicating that the result has significant value again inflation in the long term. While in Conventional side M1 value is 4.70475, that’s mean the result has significant too against inflation, cause the value both of them bigger than T Table. Another variable such as the exchange rate for the long term has negative influence to the inflation around -18.28331 which means exchange rate has significant influence to the inflation. Both of the last variables are interest and return sharia’ has significant too again inflation, the value around 0.443061 for interest rate, and 2.389915 for return sharia. It means both of these variables has significant values again inflation, cause of T Statistic bigger than T Table.